2019
DOI: 10.1002/eat.23138
|View full text |Cite
|
Sign up to set email alerts
|

Variability in remission in family therapy for anorexia nervosa

Abstract: Objective The evolution toward more stringent conceptualizations of remission in family therapy for adolescent anorexia nervosa (AN) has, with time, introduced variability in outcomes across randomized controlled trials (RCTs). An examination of remission across the history of research on family therapy for AN shows that earlier studies adopted lenient definitions and generally yielded higher rates of remission than studies of the past decade that have used stricter definitions of remission. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…For adolescents with anorexia nervosa (AN), current evidence supports family-based treatment [FBT (4)] preferably within a specialist multidisciplinary service (5)(6)(7). Despite its strong evidence base (8), FBT only achieves full remission in approximately one third of adolescents, although partial remission rates are higher (9)(10)(11)(12). Treatment engagement can be especially challenging for families and clinicians given the egosyntonic nature of AN (13) and the intense demands of FBT for the family.…”
Section: Introductionmentioning
confidence: 99%
“…For adolescents with anorexia nervosa (AN), current evidence supports family-based treatment [FBT (4)] preferably within a specialist multidisciplinary service (5)(6)(7). Despite its strong evidence base (8), FBT only achieves full remission in approximately one third of adolescents, although partial remission rates are higher (9)(10)(11)(12). Treatment engagement can be especially challenging for families and clinicians given the egosyntonic nature of AN (13) and the intense demands of FBT for the family.…”
Section: Introductionmentioning
confidence: 99%
“…Remission rates are particularly promising for adolescents with short illness duration [ 11 , 16 , 21 ]. The average remission rate for all participants at the end of FBT is approximately 40% [ 11 , 22 , 23 ]. An average of 75% of young people demonstrate improvement in weight and eating-related symptomatology at end of FBT [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although family-based treatments have a promising evidence-base [29], a large proportion of patients and families participating in clinical trials fail to achieve remission [25,30,31]. A more modest outcome becomes especially visible when strict remission criteria are applied [3]. Consequently, several questions remain on how we can optimize treatment to enable a better fit for both the young person and his and her family.…”
Section: Discussionmentioning
confidence: 99%
“…Recovery from anorexia nervosa (AN) is not universally defined in the literature [1], and quantitative research has demonstrated that recovery rates vary exceedingly depending on the definition used [2,3]. Moreover, recovery can be approached from several positions, as treatment providers, researchers and people with a lived experience may support different definitions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation